As we have always done: Indigenous freedom through radical resistance - Simpson, Leanne Betasamosake (University of Minnesota Press, 2017)
Across North America, Indigenous acts of resistance have in recent years opposed the removal of federal protections for forests and waterways in Indigenous lands, halted the expansion of tar sands extraction and the pipeline construction at Standing Rock, and demanded justice for murdered and missing Indigenous women. In As We Have Always Done, Leanne Betasamosake Simpson locates Indigenous political resurgence as a practice rooted in uniquely Indigenous theorizing, writing, organizing, and thinking. Indigenous resistance is a radical rejection of contemporary colonialism focused around the refusal of the dispossession of both Indigenous bodies and land. Simpson makes clear that its goal can no longer be cultural resurgence as a mechanism for inclusion in a multicultural mosaic. Instead, she calls for unapologetic, place-based Indigenous alternatives to the destructive logics of the settler colonial state, including heteropatriarchy, white supremacy, and capitalist exploitation.
Keywords: amérique du nord; amériques; approches et analyses; autochtones; colonialisme; com5170; cours; discours dominant; fem1300; histoire et politique; militance; pol4212; premier cycle; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne Betasamosake; Régimbald, Anne-Marie (Varia, 2018)
"On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale."– Renaud-Bray.
Section: 216 pages ; 21 cm.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; militance; ojibwa; premier cycle; premières nations; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires